Dismantling everyday discrimination : microaggressions toward LGBTQ people - Nadal, Kevin L.; American Psychological Association (Washington, USA: American Psychological Association, 2023)
"This book examines the microaggressions that LGBTQ people face on a daily basis, highlights their impact on mental health, and discusses ways mental health providers can help clients process and address microaggressions. In contrast to outright assaults and hate crimes, microaggressions are typically more covert or innocuous in nature-sometimes intentional or unintentional-communicating hostile, insulting, or negative messages about people of oppressed groups. Since the first edition of this book (That's So Gay!: Microaggressions and the Lesbian, Gay, Bisexual, and Transgender Community) was published, there has been a cultural shift towards the acceptance of LGBTQ people in some parts of the United States. Yet many state governments have also passed laws that attack and discriminate against LGBTQ people, while institutional and interpersonal discrimination continues to occur in the lives of LGBTQ people throughout the country. This book includes a comprehensive overview of empirical work on microaggressions against LGBTQ people. Mental health practitioners can use the book to understand how microaggressions negatively affect their clients' lives, enabling them to build stronger therapeutic relationships and develop appropriate treatment plans. Educators can use this book to instruct their students, trainees, and colleagues about heterosexism, genderism, and microaggressions. It is a helpful resource for insight into workplace dynamics, and it can also be useful for lay readers of all backgrounds"--
Machine generated contents note: Dedication -- Acknowledgements -- Preface -- An Introduction to Microaggressions: Understanding Definitions and Impact -- Chapter 1: A Brief History of LGBTQ People and Civil Rights -- Chapter 2: A Review of Microaggression Literature -- Chapter 3: Sexual Orientation Microaggressions: Experiences of Queer, Lesbian, Gay, Bisexual, and Pansexual People -- Chapter 4: Gender Identity Microaggressions: Experiences of Transgender, Gender Nonconforming, and Nonbinary People -- Chapter 5: Intersectional Microaggressions: Experiences of LGBTQ People of Color -- Chapter 6: Intersectional Microaggressions: Experiences of LGBTQ People with Disabilities, LGBTQ People of Diverse Sizes, Older LGBTQ People, and LGBTQ Youth -- Chapter 7: Intersectional Microaggressions: Experiences of LGBTQ Religious and Non-Religious People, LGBTQ Immigrants, and LGBTQ Poor and Working-Class People -- Chapter 8: The Processes of Dealing with Microaggressions: Considerations for Targets and Allies -- Chapter 9: Conclusion: Recommendations for LGBTQ People, Allies, and Upstanders -- References -- Index -- About the Author -- .
Includes bibliographical references and index.
Keywords: Discrimination; Social Problem; Psychology; Sex; Sociology; Sexual minorities -- Mental health; Sexual minorities -- Psychology; Microaggressions